Ethnic discrimination against African Americans in the United States - Trinh, Thi Thu Phuong (2020)
This research is an attempt to provide a deep look on the racial discrimination against African American in the United States as an international issue which has taken much concern from all races over the world. By examining how the black were discriminated in three basic areas of life such as economy, politics and education before 21st century, this study reveals the real improvements in the lives of black Americans so far and efforts to eliminate discrimination reflected through a range of positively political policies. Thus, this paper involves the summary, collation and synthesis of existing research including previous research reports, newspapers, magazines and journal content, and government statistics on ethnic discrimination against African Americas in the United States. The findings reveal that although suffered from poverty, unemployment, and lack of political power, the African American have gradually overcome many obstacles to get their freedom, to gain their position as equal as others